Fruit consumption by Trachops coffini (Chiroptera: Phyllostomidae) in Guatemala - Salguero García, Diana; Mansilla García, Diana; Sosa, Lesly E.; Trujillo, Luis A. (Therya Notes, 2026)
Carnivorous bats in the Neotropics, such as Trachops coffini (Phyllostomidae), are typically considered strict predators of small vertebrates and invertebrates. Nonetheless, isolated reports of frugivory have been reported in some carnivorous phyllostomid bats. Here, we report the first documented case of fruit consumption by T. coffini in Guatemala. This frugivory event was recorded during nocturnal mist-netting surveys conducted in the Selempín Nature Reserve, El Estor, Izabal, Guatemala. Captured individuals were temporarily held in cloth bags, and fecal samples were collected and examined under a stereomicroscope to assess dietary content. On November 23, 2024, three individuals of T. coffini were captured. Seeds of Ficus maxima were recovered from the feces of one individual. This finding provides direct evidence of dietary flexibility in T. coffini and is consistent with previous reports of frugivory in other carnivorous phyllostomid bats, including T. cirrhosus (now restricted to South America), Chrotopterus auritus, and Vampyrum spectrum.